Impact of investor sentiment on firm innovation: Evidence from textual analysis - Zihao Lin (Borsa İstanbul Review, 2023)
The paper examines whether and how investor sentiment affects corporate innovation. The study finds a statistically significant relationship between investor sentiment and firm innovation. Our findings demonstrate that investor sentiment has a positive causal impact on firm innovation, as revealed through the use of the instrumental variable method and propensity score matching approach, as well as the use of changes in investor sentiment as independent variables. The results still hold after using alternative measures of investor sentiment. Our subsample analysis indicates that investor sentiment boosts innovation, regardless of R&D ratios. The estimated results after considering changes in economic conditions remain consistent with the baseline estimates. The mechanism analysis suggests that investor sentiment alleviates financing constraints and enhances R&D investment, thereby positively impacting firm innovation.
Keywords: 330; Corporate innovation; Financing constraints; Investor sentiment; Textual analysis